Are companies responding to minimum wage increases by reducing corporate social responsibility? - Hao Wang; Tao Zhang; Xi Wang (PLoS ONE, 2025)
Corporate social responsibility (CSR) has been widely discussed. However, the existing literature does not delve into the theoretical mechanism to show how companies adjust their CSR in the face of minimum wage increases. This may be due to the lack of a theoretical framework that clarifies the relationship between minimum wage increases and CSR adjustments. The objectives of this study is to fill this gap by investigating the impact of minimum wage increases on CSR, employing both cost stickiness and optimal distinctiveness theories. We use the data from the CSMAR database, the Human Resources and Social Security Administration, and Hexun rating system. The subject of this study is China’s A-share listed companies during 2010–2020. This study employs fixed-effects models for a panel data. The findings reveal that minimum wage increases are significantly associated with a reduction in both strategic CSR and responsive CSR. Notably, the decrease in responsive CSR outweighs that of strategic CSR. Furthermore, our results indicate that customer concentration or CSR sensitivity significantly moderates this relationship. More particularly, firms with higher customer concentration are less responsive to minimum wage increases in their CSR activities. Firms with higher sensitivity in CSR are more likely to mitigate the reducing effect of the minimum wage on CSR. By revealing how minimum wage increases affect CSR and its economic consequences, our study provides scientific recommendations for policymakers to measure the impact of minimum wage policies at the firm level.